2023
DOI: 10.1039/d3cy00832k
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear chromium complexes with [OSSO]-type ligands in the copolymerization of epoxides with CO2and phthalic anhydride

Abstract: In this study, a new family of dinuclear chromium complexes (1-3) containing bis-thioether-diphenolate ligands has been introduced for the copolymerization of epoxides with carbon dioxide and with phthalic anhydride. Catalyst...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…[48,49] In our previous study, we observed similar behaviour in the terpolymerization PO/CO 2 /PA activated by the 1/PPNCl system. [44] This observation reaffirms the high regioselectivity of complex 1 during the terpolymerization reaction. Switching from SA to diglycolic anhydride (DGA) showed improved catalytic activity for 1/PPNCl in the terpolymerization reaction with PO/CO 2 /DGA, even at a lower temperature of 45 °C.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…[48,49] In our previous study, we observed similar behaviour in the terpolymerization PO/CO 2 /PA activated by the 1/PPNCl system. [44] This observation reaffirms the high regioselectivity of complex 1 during the terpolymerization reaction. Switching from SA to diglycolic anhydride (DGA) showed improved catalytic activity for 1/PPNCl in the terpolymerization reaction with PO/CO 2 /DGA, even at a lower temperature of 45 °C.…”
Section: Resultssupporting
confidence: 57%
“…Terpolymerization of Epoxide/CO 2 /Cyclic Anhydride The [OSSO]-type pro-ligand and the corresponding dinuclear metal complexes 1 and 2 (Scheme 2) were synthesized and fully characterized according to our prior reported work. [43,44] The optimized conditions for terpolymerization of epoxide/carbon dioxide with cyclic anhydride were found for catalyst loading 0.10 mol % and (bis(triphenylphosphine)iminium chloride) (PPNCl, 0.5-1.0 mol), and p CO 2 = 20 bar by following our previous work. [44] In our initial terpolymerization experiment, we reacted propylene oxide (PO) and aliphatic succinic anhydride (SA) in a 10 : 1 molar ratio with carbon dioxide, catalyzed by 1/PPNCl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, the order of 2 was similar to the results of some bimetallic complexes, supporting the involvement of two metal centers during the polymerization process. Different reaction orders were also found in the reported iron(III)-alkoxide complexes and chromium complexes, implying that there were probably different reaction pathways for the ROP of CHO initiated by dinuclear complex 2 and mononuclear complex 1 .…”
Section: Resultsmentioning
confidence: 91%